Abnormalities of insular functional connectivity in patients with musculoskeletal pain: A meta-analysis of resting-state fMRI studies - Peng Lai; Xingyao Chen; Jiacheng Liu; Zilei Tian; Yangke Mao; Chenyang Jia; Siting Ma; Deliang Zhu; Ming Xin; Fang Zeng; Shirui Cheng (Brain Research Bulletin)
Background: Resting-state functional magnetic resonance imaging (fMRI) studies have shown abnormal functional connectivity (FC) of the insula (INS) in patients with musculoskeletal pain (MSP). However, there is a lack of consistency in previous studies, which is an obstacle to understanding the underlying neuropathology of MSP. Method: Seven databases, including PubMed, Web of Science, the Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), Wanfang Database, and Chongqing VIP, were systematically searched from inception to 15 May 2024. The meta-analysis of the aberrant INS-based FC in MSP patients was performed using the anisotropic effect-size signed differential mapping (AES-SDM). Results: A total of eleven neuroimaging studies with 276 patients and 253 HCs were included in the meta-analysis. The results indicate that MSP patients have increased FC between INS and the right median cingulate gyri, right inferior frontal gyrus, right paracentral lobule, and right supplementary motor area, and decreased FC between INS and the right posterior cingulate gyrus, left precuneus, and left angular gyrus. Heterogeneity and sensitivity analysis showed that most of the results of INS-based FC were highly reproducible and robust. Meta-regression analysis showed that revealed a negative association between the Visual Analog Scale (VAS) score and the reduction in FC between the INS and the left precuneus. Conclusion: The meta-analysis reveals that patients with MSP show abnormal FC between the INS and multiple brain regions, which are involved in emotional, cognitive, sensory, visuospatial and motor regulation of pain. These findings provide important insights into the underlying neuropathological mechanisms of musculoskeletal disorders.